Waltharius and Carolingian morality: satire and lay values. Issue 1 (7th January 2013) - Stone, Rachel
<x xml:space="preserve">Abstract</x> Some recent interpretations of the early medieval Latin poem Waltharius have seen it as offering a clerical critique of warrior culture. While the poem is difficult to date accurately, it seems more likely to belong to the ninth than the tenth century. When the poem is analysed in the context of contemporary Frankish works providing moral instruction to lay noblemen, its attitudes towards pride, wealth and warfare can be shown to lie within the mainstream of Carolingian reformers' thought. The notoriously bloody ending to the poem is also best seen as emphasizing Walter's successful heroism rather than undermining it.